Toxicity to Rhinella arenarum tadpoles (Anura, Bufonidae) of herbicide mixtures commonly used to treat fallow containing resistant weeds: glyphosateedicamba and glyphosateeflurochloridone - Ruiz de Arcaute, Celeste (2020)
Glyphosate (GLY)-dicamba (DIC) and GLY-flurochloridone (FLC) are herbicide mixtures which are widely used for treating fallow containing glyphosate resistant weeds. The aim of this study was to evaluate the acute toxic effects and the prevailing interactions on stage 36 tadpoles of the anuran species Rhinella arenarum when exposed to equitoxic and non-equitoxic combinations of these herbicide combinations. Experiments were realized using the following combinations of commercial formulations: 48% GLYbased Credit® þ 57.71% DIC-based Banvel® and 48% GLY-based Credit® þ 25% FLC-based Twin Pack Gold®. GLY-DIC and GLY-FLC equitoxic mixtures were assayed mixing each constituent with an equivalent individual toxicity able to induce the same lethality effect. After 96 h of exposure, GLY-DIC and GLY- FLC equitoxic mixtures presented toxic unit 50 values (TU50 96h) of 1.74 (confidence interval: 1.58e1.92) and 1.54 (confidence interval: 1.46e1.62) respectively, indicating the presence of a weak antagonistic interaction as TU values were greater than 1. For their part, most non-equitoxic combinations of GLY-DIC and GLY-FLC tested did not significantly differ from additivity, the only exception being when DIC and FLC were fixed at 0.33 TUs, where a weak antagonism was observed. Overall, results indicate that the toxicity